Use of methamphetamine and alcohol among people with opioid use disorder and HIV in Vietnam: a qualitative study - Andrew Edsall; Kim A. Hoffman; Dinh Thanh Thuy; Pham Phuong Mai; Nguyen Thu Hang; Tong Thi Khuyen; Nguyen Thu Trang; Lynn E. Kunkel; Le Minh Giang; P. Todd Korthuis (BMC, 2021)
Abstract Background Heroin use continues to drive HIV transmission in Vietnam, but methamphetamine and alcohol use are growing rapidly and, as in other countries, polysubstance use is widespread. The objective of this study was to understand the interplay between heroin, methamphetamine, and alcohol use among people with opioid use disorder (OUD) and HIV in Vietnam. Methods We conducted 44 in-depth, face-to-face qualitative interviews with people with OUD and HIV who participated in the BRAVO trial of buprenorphine versus methadone in five Vietnam HIV clinics. Interviews probed participants' experiences of heroin, methamphetamine, and alcohol use and their interplay with HIV/OUD treatment. Interviews were professionally transcribed and analyzed using a thematic analysis approach. Results Of 44 participants interviewed 42 were male, on average 38.8 years of age, with 30 reporting a history of methamphetamine use and 33 reporting a history of alcohol use. Several themes emerged: 1) Methamphetamine and alcohol were perceived to have lower addiction potential than heroin 2) Social settings were key facilitators of alcohol and methamphetamine use 3) Some participants, but not all, used methamphetamine to help quit heroin 4) Consuming alcohol blunted the effects of heroin, while paradoxically serving as a catalyst for heroin use 5) Use of methamphetamine was perceived by many participants to be incompatible with treatment for HIV. Conclusions Participant experiences reflected a significant impact of polysubstance use on treatment of HIV and OUD. Patterns of polysubstance use are subject to common preconceptions of alcohol and methamphetamine as having a low addictive potential, and these substances are deeply enmeshed in the social life of many people with OUD in Vietnam. Interventions to address complex social norms and potential harms of polysubstance use are urgently needed as the population of people receiving medication for OUD (MOUD) increases in Vietnam and globally. Trial registration BRAVO - NCT01936857 , September 2013.